A retrospective cohort study of hypertension, cardiovascular disease, and metabolic syndrome risk in women with history of preterm and term preeclampsia five years after delivery - Aditiawarman, - (Elsevier, 2023)
Objectives To evaluate maternal hypertension, risk of cardiovascular disease (CVD), and metabolic syndrome five years after delivery in preterm preeclampsia (P-PE), term preeclampsia (T-PE), and normal pregnancy. Study design This was a retrospective cohort study of women who delivered at Dr. Soetomo Academic Hospital (Indonesia) in 2013 with a diagnosis of PE and were compared with women with normal pregnancies. Main outcomes measures Blood pressure, National Cholesterol Education Program Adult Treatment Panel III criteria for metabolic syndrome (NCE-ATP III), and Framingham Risk Score (FRS). Results In this study, 92 women participated. They were divided into the P-PE (27), T-PE (35), and control groups (30). Women with a history of PE, P-PE, or T-PE had higher blood pressure five years after delivery than those in the control group (p < 0.05). Systolic blood pressure (SBP) >140 mmHg was seen in 66.7% of P-PE and 25.7% of T-PE, while 55.6% of P-PE and 34.3% of T-PE had diastolic blood pressure (DBP) >90 mmHg (p < 0.05). Women with P-PE had the highest risk of developing hypertension (Relative risk (RR): 20; 95% Confidence interval [CI]: 2.85–139.92). Women with history of P-PE (RR: 1.85; 95% CI: 0.77–4.41), T-PE (RR: 1.28; 95% CI: 0.51–3.19), and total PE (RR: 1.53; 95% CI: 0.68–3.43) had an increased risk of positive NECP-ATP III five years after delivery. Women with history of P-PE (RR: 5.17; 95% CI: 0.26–103.22; p = 0.282) and T-PE (RR: 6.03; 95% CI: 0.32–112.22; p = 0.228) are at a greater risk of having an FRS >10% compared to the control group (p = 0.04). Conclusions History of PE, P-PE, and T-PE increased the risk of hypertension and CVD five years after delivery. The results also showed a tendency toward an increased risk of metabolic syndrome in women with a previous history of PE and P-PE.